Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)